Pharmaceutical Industry Influencers and Stock Price Analysis on the Indonesia Stock Exchange - Syaiful, Syaiful; Hidayat, Rahmat; Yolanda, Yolanda; Savira, Erika Putri (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This study explains the effect of financial ratios on stock prices in pharmaceutical companies listed on the Indonesia Stock Exchange. This study used panel regression analysis, where time series (2016-2022) and cross-section (8 Pharmaceutical companies). Data analysis techniques using Ordinary Least Squares regression (OLS) and selection of the best model through the Chow test and Hausman test with fixed effect model as the best model. Based on the results of the calcic assumption test, the selected model is appropriate and valid for analysis. The results of the analysis show that Return On Assets, Return On Equity, Net Profit Margin, and Debt to Equity Ratio to Stock Price have a positive and significant effect both simultaneously and partially. The variation in the ability of the independent variable in this study affects the stock price variable by 88.15% and the effect is strong. Recommend to the Board of Directors of Pharmaceutical Companies listed on the Indonesia Stock Exchange to introduce policies that will have a positive impact on return on equity, earnings per asset, and debt to equity that can significantly affect the stock price.